Mannheimia haemolytica serovars associated with respiratory disease in cattle in Great Britain - Colin Mason; Jane Errington; Geoffrey Foster; Jennifer Thacker; Oliver Grace; Katharine Baxter-Smith (BMC Veterinary Research, 2022)
Abstract Background Mannheimia haemolytica is commonly associated with respiratory disease in cattle worldwide as a cause of fibrinous pneumonia, bronchopneumonia and pleuritis. M. haemolytica is further subdivided into 12 serovars, however not all are considered to be pathogenic in cattle. The study aim was to determine the most common serovars of M. haemolytica associated with respiratory disease in cattle in Great Britain, which is currently unknown and could be useful information for clinicians when considering preventative strategies. Results One hundred four M. haemolytica isolates isolated from bovine clinical pathology and post-mortem samples from pneumonia cases between 2016 and 2018 were tested using a multiplex PCR assay to identify M. haemolytica serovars A1, A2 and A6. 46 isolates (44.2%) typed as M. haemolytica serovar A1, 31 (29.8%) as M. haemolytica serovar A2 and 18 isolates (17.3%) as M. haemolytica serovar A6. Nine isolates (8.7%) were not A1, A2 or A6 so were considered to belong to other serovars or were not typable. Conclusion This study highlights the importance of M. haemolytica serovars other than A1 which may be responsible for respiratory disease in cattle and could help guide the veterinarian when making choices on preventative vaccination programmes.